Blood mercury, lead, cadmium, manganese and selenium levels in pregnant women and their determinants: the Japan Environment and Children’s Study (JECS) - Nakayama, Shoji F. (J Expo Sci Environ Epidemiol, 2019)
The Japan Environment and Children’s Study (JECS) is a birth-cohort study of 100,000 mother–child dyads that aims to investigate the effect of the environment on child health and development. Mercury (Hg), lead (Pb), cadmium (Cd), manganese (Mn) and selenium (Se) are considered to be important co-exposures when examining the effect of other chemical substances on child development. The levels of these elements in the blood of 20,000 randomly selected mid/late-term pregnant women from the whole JECS cohort were analysed using inductively coupled plasma-mass spectrometry. The median concentrations (interquartile ranges) for Pb, Hg, Cd, Mn and Se were 0.63 (0.51–0.78) µg dl(−1), 3.83 (2.70–5.43) µg l(−1), 0.70 (0.52–0.95) µg l(−1), 16.1 (13.2–19.6) µg l(−1) and 178 (165–192) µg l(−1), respectively. Hg and Se correlated positively with each other (Spearman’s ρ = 0.287), as did Pb and Cd (ρ = 0.239) and Cd and Mn (ρ = 0.267). The blood Pb levels decreased by 5–10-fold over the past 25 years. The main predictors of the blood levels of each element were fish consumption for Hg, maternal age and non-alcoholic beverage consumption for Pb, maternal age and smoking for Cd, gestational age at sampling for Mn and serum protein levels for Se. These results revealed the historical trends and current predictors of the blood levels of these elements in pregnant Japanese women.